THE PREVALENCE OF HELICOBACTER PYLORI INFECTION IN PATIENTS UNDERGOING OESOPHAGO-GASTRODUODENOSCOPY IN PERAK, MALAYSIA - Venkatesh CS; Wong SK; Hassan AKR; Yan YW; Chan CP; Ebernesan B (Asian Journal of Medicine & Health Sciences, 2019)
Helicobacter pylori has been established as the pathogen responsible for various upper gastrointestinal conditions ranging from peptic ulcer disease to malignancies such as gastric adenocarcinoma and mucosa associated lymphoid tissue lymphoma. In this study the prevalence of this organism among patients undergoing oesophago-gastro-duodenoscopy as outpatients was investigated utilizing the rapid urease test of endoscopic gastric biopsies. Out of 278 respondents, we discovered that the prevalence was 40.3% with a slight female preponderance. Ethnic differences were also noted with a much higher (>40%) percentage of Indians and Chinese testing positive for the organism compared with the Malays (23.8%). A larger proportion of the respondents who had the organism were found to have positive OGDS findings compared with those who did not have the organism.